Impacts of stress and sex hormones on dopamine neurotransmission in the adolescent brain - Sinclair, Duncan (Springer Berlin Heidelberg, 2014)
RATIONALE: Adolescence is a developmental period of complex neurobiological change and heightened vulnerability to psychiatric illness. As a result, understanding factors such as sex and stress hormones which drive brain changes in adolescence, and how these factors may influence key neurotransmitter systems implicated in psychiatric illness, is paramount. OBJECTIVES: In this review, we outline the impact of sex and stress hormones at adolescence on dopamine neurotransmission, a signaling pathway which is critical to healthy brain function and has been implicated in psychiatric illness. We review normative developmental changes in dopamine, sex hormone, and stress hormone signaling during adolescence and throughout postnatal life, then highlight the interaction of sex and stress hormones and review their impacts on dopamine neurotransmission in the adolescent brain. RESULTS AND CONCLUSIONS: Adolescence is a time of increased responsiveness to sex and stress hormones, during which the maturing dopaminergic neural circuitry is profoundly influenced by these factors. Testosterone, estrogen, and glucocorticoids interact with each other and have distinct, brain region-specific impacts on dopamine neurotransmission in the adolescent brain, shaping brain maturation and cognitive function in adolescence and adulthood. Some effects of stress/sex hormones on cortical and subcortical dopamine parameters bear similarities with dopaminergic abnormalities seen in schizophrenia, suggesting a possible role for sex/stress hormones at adolescence in influencing risk for psychiatric illness via modulation of dopamine neurotransmission. Stress and sex hormones may prove useful targets in future strategies for modifying risk for psychiatric illness.